Autoimmune Factor V Deficiency That Took 16 Years to Diagnose due to Pseudodeficiency of Multiple Coagulation Factors. (12th January 2021) - Kato, Takaaki; Hanawa, Takaya; Asou, Mea; Asakawa, Tomohiko; Sakamaki, Hisashi; Araki, Makoto
Abstract : A 70-year-old man presented to our hospital with intramuscular hemorrhage in the right thigh. He had exhibited a tendency to bleed for the last 16 years and had visited several medical institutions, but no diagnosis had been made. Since the risk of sudden bleeding was assumed to be high due to his age, we decided to examine him in our department. A coagulation abnormality with prothrombin time-international normalized ratio (PT-INR) of 4.5 and activated partial thromboplastin time (aPTT) of 99.6 seconds was observed, but the platelet count, fibrinogen, and PIVKAII were within normal limits. Coagulation activities of factor V, VII, VIII, IX, X, XI, XII, and XIII were all reduced. Anti-factor VIII and IX antibodies which were measured by the Bethesda method, lupus anti-coagulant (diluted Russell snake venom time method) and anti-cardiolipin antibody were also positive. The results of these tests were comparable to those undertaken 15 years ago when they were scrutinized at the university hospital. We suspected the presence of anti-factor V antibodies because there was a dissociation between the thrombotest values measured and those calculated from the PT-INR. Moreover, cross-mixing test showed an immediate inhibitor pattern. Subsequently, factor V antibodies were confirmed by the immunoblot method and the diagnosis of autoimmune factor V deficiency was made. When factor V, which is downstream of the coagulation cascade, is inhibited, coagulation test using the one-stage clotting method shows a pseudolow value. Therefore, extensive abnormalities of coagulation factor activity and inhibitor assay should be interpreted with caution, and the presence of a high titer of factor V inhibitor should be considered.